Ex Libris (Nordic Journal of Practical Theology, 2015)
Sigmund Nesset (red.):IshavskatedralenSigmund Nesset (red.):IshavskatedralenReidun Mæsel Kolvik, Johanne Seines Svendsen, SandyGoldbeck-Wood m.fl.:Pax. Fredskatedralen. Bodø domkirke